Pemanfaatan Kawasan Gunung Padang sebagai Laboratorium Lapangan Geografi - Darmawan, Cahya; Rosali, Ely Satiyasih (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2025)
Geography deals with space which includes the relationship of human intercation, interalion and interdepence with its environment. The process of learning geography is not improved by space, the natural environment can be used as a laboratory to support the learning process. The object in the Research is the Area of Gunung Padang Cianjur Regency and the subject is a student of Geography Education and Manager of Gunung Padang area. Gunung Padang can be a location to improve the skills and understanding of students related to the location of gunung padang both from the physical aspect and aspects of cultural studies. As for the process to improve the skills of students at the time of this Field Lecture Practicum activity through the stages of acquiring skills, organizing and communicating, all these skills can be fulfilled in the Practice of Geography Education Field Lecture and proven natural can be a Field Laboratory of Geography Education.